PRACTICES IN GENERATING ELEMENTARY SCHOOL STUDENTSâ LITERACY SET - Failasofah, . (Universitas Jambi, 2014)
As stated by Nunan (1999), generally, most people read books in order to get some information or for pleasure. Through reading, people are processing ideas that generated by others. Here, the ideas are transmitted through language. It happens along with listening, and assumed by some experts to become more and more important in foreign language classroom because reading provides inputs for the students. This article reviews the theoretical framework that has been adopted in some studies of elementary shcool studentsâ reading comprehension. It covers some important theories of reading, teaching reading to young learners, reading comprehension and strategies in teaching reading comprehension.